2020
DOI: 10.3389/fimmu.2020.568440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Immune Characteristics for Lung Adenocarcinoma Patients With ERLIN2 Overexpression

Abstract: BackgroundEndoplasmic reticulum lipid raft-associated protein 2 (ERLIN2) is protein contained in the membrane of the endoplasmic reticulum. In lung adenocarcinoma (LUAD), the molecular function of ERLIN2 and the correlation between ERLIN2 and tumor-infiltrating immune cells have been unclear. The aim of our study was to determine the role of ERLIN2 in LUAD development to provide a better understanding of the molecular pathogenesis of this disease and identify new therapeutic targets for its treatment.MethodsIm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The histologic grades of tumors were mostly II and III, while the AJCC stages were mostly advanced with distant metastases. A previous study ( 2 , 20 ) similarly found that 76% of lung cancer patients were old and white, more than 90% of tumors were in the upper or lower lobes of the lung, and 80–90% of AC patients among the known pathological types had poorly or moderately differentiated histologic grades ( 25 , 26 ). These characteristics are similar to those in our study.…”
Section: Discussionmentioning
confidence: 91%
“…The histologic grades of tumors were mostly II and III, while the AJCC stages were mostly advanced with distant metastases. A previous study ( 2 , 20 ) similarly found that 76% of lung cancer patients were old and white, more than 90% of tumors were in the upper or lower lobes of the lung, and 80–90% of AC patients among the known pathological types had poorly or moderately differentiated histologic grades ( 25 , 26 ). These characteristics are similar to those in our study.…”
Section: Discussionmentioning
confidence: 91%
“…described as an antisense transcript of ERLIN2, a gene associated with juvenile primary lateral sclerosis and immune cells infiltration [53][54][55]. We found 11 and 15 genes significantly altered in the IDF and IDM comparisons, respectively; however, none displayed commonality (Figure 6, Table 7).…”
Section: Meta-analysis Of Dge In Nervous Tissuementioning
confidence: 84%
“…Importantly, ERLIN2 mutations lead to abnormal splicing and nonsense-mediated mRNA decay, promoting motor neurodegeneration and juvenile amyotrophic lateral sclerosis [55]. Additionally, ERLIN2 has been related to the infiltration of immune cells in the tumor microenvironment [54]. Therefore, LOC102723701 may represent an exciting and novel target in MS for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The abundances of B cells, plasma cells, resting memory T cells CD4, resting NK cells, monocytes, M2 macrophages, resting DCs, resting mast cells, and neutrophils were substantially different between high and low riskscore group. Ample evidence has shown that the infiltration of B cells, especially naive B cells, memory B cells, and plasma cells is associated with a good prognosis of LUAD ( 38 ). In contrast, we found the high-risk subgroup had a poor prognosis while high plasma cell expression.…”
Section: Discussionmentioning
confidence: 99%